Functional Suitability Analysis of Remote Laboratories in Engineering Education. (2016) - German-Sallo, Zoltan; Grif, Horatiu-Stefan; Gligor, Adrian
Abstract: This paper presents an evaluation strategy and method which is applied to characterize from a technical point of view a set of remote laboratories. These remote laboratory experiments are set in the Maghrebian countries (Morocco, Algeria, and Tunisia) and serve as teaching materials in engineering education. The technical evaluation strategy is based on guidelines defined by specific standards. According to this standard, the product quality model categorizes product quality properties into eight characteristics (functional suitability, reliability, performance efficiency, usability, security, compatibility, maintainability and portability). Each characteristic is composed of a set of related sub-characteristics. The performed technical evaluation focuses on functional suitability but is only concerned with whether the functions meet stated and implied needs, not the functional specification and does not deal with pedagogical outcomes; these were evaluated by another group of specialists. The main goal of this evaluation is to find and quantify measurable parameters in order to have functional suitability analysis tools.